Gaseous Adsorption in Melanins: Hydrophilic Biomacromolecules with High Electrical Conductivities - Paul Meredith (Langmuir, 2010)
The melanins are an important class of multifunctional biomacromolecules that possess a number of intriguing physical and chemical properties including electrical and photoconductivity. Unusually for a conducting organic material, eumelanin is hydrophilic and its electrical properties are strongly dependent on its hydration state. We have therefore measured adsorption isotherms for two polar adsorbates, water and ethanol, in the pressed powder pellets of synthetic eumelanin typically used in electrical studies. We show that a simple kinetic monolayer Langmuir model describes the adsorption and find that there are strong adsorbate−eumelanin interactions in both cases. These isotherms allow the proper scaling of electrical conductivity data and in doing so make progress toward a better understanding of eumelanin electrical properties, which is a critical prerequisite to the design of new eumelanin-like bioelectronic materials.